Analysis of Gay Language and Slang in Bali - Farahdila, Jesika; Adni, Nissa Puspitaning (CV. Ulil Albab Corp, 2024)
In community, people may use different language variation accordance with their age, gender, education, profession, ethnic origin, etc. (Holmes, 2013). The purpose of this study was to examine the linguistic features, derivation, and function of languages ​​used by homosexual and bisexual men in Bali, Indonesia. In identifying the linguistic features of gay language, the researcher analyzed the data taken from the respondents from their simulation and list of gay words. The important role of creativity and language skills can be developed and enhanced through frequent use of language. The impact on gay language use is to create identities for gay communities, develop self-expression, provide exclusive spaces through obfuscation, and find their own comfort zones. language. The study also found that gay language serves many functions for their communities. These features included being a secret language, a community identity, a language that conveys similarities and a sense of belonging to community members. Homosexual language also served to show humor, helping people speak in a more friendly and fun way.